Along‐Axis Variations of Rift Width in a Coupled Lithosphere‐Mantle System, Application to East Africa. Issue 11 (5th June 2018) - Koptev, Alexander; Calais, Eric; Burov, Evgueni; Leroy, Sylvie; Gerya, Taras
Abstract: Narrow and wide rifts are end‐member expressions of continental extension. Within the framework of passive rifting, the transition from wide to narrow rifts requires lowering the geothermal gradient. Reconciling this view with observational evidence for narrow rift zones in regions underlain by sublithospheric hot plume material, such as the eastern branch of the East African Rift, requires invoking preexisting weak zones for strain to localize in a warm crust. Based on thermomechanical numerical models, we show that along‐rift width variations can develop spontaneously as a consequence of spatial variations of the geotherm over an evolving mantle plume impinging a lithosphere subjected to ultraslow extension. The eastern branch of the East African Rift, with a narrow Kenya segment underlain by a mantle plume head and widening to the north and south in the colder regions of the Turkana depression and North Tanzania divergence, is in agreement with this numerical prediction. Plain Language Summary: This study is inspired by a contradiction between the usual inference from passive rifting models that predict a transition from narrow to wide rifts correlated with increasing lithospheric temperatures, while observations in the eastern branch of the East African Rift show that its narrowest segment is underlain by a deep‐seated positive thermal anomaly. We present the results from 3‐D thermomechanical numerical experiments showing that narrow rifting, conventionally attributed to "passive" rifting of cold and strong lithosphere, can also develop in hot and weak lithosphere in the case of plume‐assisted rifting, as observed in the Kenyan rift. Preexisting lithospheric structures are not required to determine and control rift initiation and development, in contrast to the classical interpretation based on passive models that require preexisting rheologically weak zones to initiate and guide fault propagation. Key Points: Impingement of a mantle plume under a lithosphere subjected to tension focuses brittle strain in the crust Rift width variation results from spatial variations of the lithospheric geotherm associated with the evolving mantle plume Modeled strain localization is consistent with the observed transition from the narrow Kenya rift to broader rifts to the north and south